Loans and employment: Evidence from bank-specific liquidity shocks - Román Acosta; Josué Cortés (Latin American Journal of Central Banking (LAJCB), 2022)
This paper investigates the relationship between expansionary credit events and firms' employment decisions. To overcome the endogeneity coming from the supply side of credit we exploited the legal and political framework in Mexico to examine the effects of local governments' prepayment of loans, a situation that leads banks to channel newfound liquidity in firms. Analysis of a novel data set covering a 10-year period showed that a 1-standard-deviation increase in the issuance of new loans increases firms' employment by 2.57 percentage points. Timing of the boost in employment varies, with smaller firms reacting immediately and larger firms reacting four months later. The effects are driven by firms in the manufacturing sector. Our results highlight the importance of the bank lending channel to stimulate employment in the short term, especially for smaller firms. Further, our estimates suggest that the effect of credit on employment could be amplified with policies that promote a more competitive corporate loan market.
Keywords: 330; Bank lending channel; Corporate loans; Employment